173k views
10 votes
2x^3-x^2-3x=210
the answer is 5 but I want to know why.

2 Answers

5 votes
You want to know why what?
User Iqbalzas
by
5.2k points
6 votes

Answer:


x=5,(-9+√(255)i )/(4) ,(-9-√(255)i )/(4)

Explanation:

1) Move all terms to one side.


2x^(3) -x^(2) -3x-210=0

2) Factor
2{x}^(3)-{x}^(2)-3x-210 using Polynomial Division.

1 - Factor the following.


2x^(3) -x^(2) -3x-210

2 - First, find all factors of the constant term 210.


1,2,3,4,5,6,7,10,14,15,21,30,35,42,70,105,210

3) Try each factor above using the Remainder Theorem.

Substitute 1 into x. Since the result is not 0, x-1 is not a factor..


2*1^(3) -1^(2) -3*1-210=-212

Substitute -1 into x. Since the result is not 0, x+1 is not a factor..


2(-1)^(3) -(-1)^(2) -3*-1-210=-210

Substitute 2 into x. Since the result is not 0, x-2 is not a factor..


2*2^(3) -2^(2) -3*2-210=-204

Substitute -2 into x. Since the result is not 0, x+2 is not a factor..


2{(-2)}^(3)-{(-2)}^(2)-3* -2-210 = -224

Substitute 3 into x. Since the result is not 0, x-3 is not a factor..


2* {3}^(3)-{3}^(2)-3* 3-210 = -174

Substitute -3 into x. Since the result is not 0, x+3 is not a factor..


2{(-3)}^(3)-{(-3)}^(2)-3* -3-210 = -264

Substitute 5 into x. Since the result is 0, x-5 is a factor..


2* {5}^(3)-{5}^(2)-3* 5-210 =0

------------------------------------------------------------------------------------------


x-5

4) Polynomial Division: Divide
2{x}^(3)-{x}^(2)-3x-210 by
x-5.


2x^(2)
9x
42

-------------------------------------------------------------------------


x-5 |
2x^(3)
-x^(2)
-3x
-210


2x^(3)
-10x^(2)

-----------------------------------------------------------------------


9x^(2)
-3x
-210

--------------------------------------------------------------------------


42x
-210


42x
-210

-------------------------------------------------------------------------

5) Rewrite the expression using the above.


2x^2+9x+42


(2x^2+9x+42)(x-5)=0

3) Solve for
x.


x=5

4) Use the Quadratic Formula.

1 - In general, given
a{x}^(2)+bx+c=0 , there exists two solutions where:


x=\frac{-b+\sqrt{b^(2) -4ac} }{2a} ,(-b-√(b^2-4ac) )/(2a)

2 - In this case,
a=2,b=9 and
c = 42.


x=(-9+√(9^2*-4*2*42) )/(2*2) ,(-9-√(9^2-4*2*42) )/(2*2)

3 - Simplify.


x=(-9+√(255)i )/(4) ,(-9-√(255)i )/(4)

5) Collect all solutions from the previous steps.


x=5,(-9+√(255)i )/(4) ,(-9-√(255)i )/(4)

User LtlBeBoy
by
5.4k points